Problems and Properties for p-Valent Functions Involving a New Generalized Differential Operator: Ala’ Ali Amourah, Tariq Al-Hawary, Maslina Darus - Team, Support (Thai Journal of Mathematics, 2017)
In this paper, a new differential operator A_p^nf(z) defined in the openunit disc U={ zC:z<1} is introduced. We then, using thisoperator and introduce a new subclass of analytic functions G(μ,λ,α,β,b,p). Moreover, we discuss coefficient estimates, growth and distortion theorems and inclusion properties for the function f belonging to the class G_n(μ,λ,α,β,b,p).